Original Sin and Reprobation in Renaissance Thomism: The Cases of Domingo Bañez and John of St. Thomas - Cai, Thomas Yilun (Nos sumus tempora, 2020)

Retrieving the Sense of the Sacred: a Paradigm of Silence in the Liturgy - Wong, Lee Chun (USJ Theses and Dissertations, 2021)
Keywords: Catholic Church; Liturgy Theology; Religious aspects Catholic Church; Silence

To follow or overcome our nature? - Cai, Yulin (GREGORIANUM, 2022)
The doctrine of original sin gives people the impression that the goodness of human nature is under-evaluated in the Christian theological tradition. The Chinese philosopher Mencius is famous for his teaching on the goodness of human nature. Reading Mencius and Thomas Aquinas side by side, this article argues that the Mencian teaching on human nature brings us to affirm the goodness of human nature by recovering the significance of the image of God for the Christian doctrine of human nature. If we seek the goodness of human nature in the possibilities to become good, it is natural to see that even in the fallen state the possibilities of becoming like God remain in human nature imprinted with the image of God. It is open to the culmination of a gradual progression to its perfection.